Corn silk (Stigma maydis) in healthcare: a phytochemical and pharmacological review - Hasanudin, Khairunnisa; Hashim, Puziah; Mustafa, Shuhaimi (MDPI, 2012)
Corn silk (Stigma maydis) is an important herb used traditionally by the Chinese, and Native Americans to treat many diseases. It is also used as traditional medicine in many parts of the world such as Turkey, United States and France. Its potential antioxidant and healthcare applications as diuretic agent, in hyperglycemia reduction, as anti-depressant and anti-fatigue use have been claimed in several reports. Other uses of corn silk include teas and supplements to treat urinary related problems. The potential use is very much related to its properties and mechanism of action of its plant’s bioactive constituents such as flavonoids and terpenoids. As such, this review will cover the research findings on the potential applications of corn silk in healthcare which include its phytochemical and pharmacological activities. In addition, the botanical description and its toxicological studies are also included.